2014
DOI: 10.1208/s12248-014-9626-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Physiologically Based Pharmacokinetic Model Informed by a Top-Down Approach for the Prediction of Pharmacokinetics in Chronic Kidney Disease Patients

Abstract: Quantitative prediction of the impact of chronic kidney disease (CKD) on drug disposition has become important for the optimal design of clinical studies in patients. In this study, clinical data of 151 compounds under CKD conditions were extensively surveyed, and alterations in pharmacokinetic parameters were evaluated. In CKD patients, the unbound hepatic intrinsic clearance decreased to a similar extent for drugs eliminated via hepatic metabolism by cytochrome P450, UDP-glucuronosyltransferase, and other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…However, CL R may reduce linearly with GFR for many drugs, even when secretion or reabsorption contributes, in accordance with the intact nephron hypothesis (63,64). (39,56).…”
Section: Assessing Dosage Adjustment In Chronic Kidney Diseasesupporting
confidence: 71%
“…However, CL R may reduce linearly with GFR for many drugs, even when secretion or reabsorption contributes, in accordance with the intact nephron hypothesis (63,64). (39,56).…”
Section: Assessing Dosage Adjustment In Chronic Kidney Diseasesupporting
confidence: 71%
“…The development of sophisticated models that allow for the simulation of multiple inhibitors or inducers, relevant metabolites, and multiple mechanisms of interaction have permitted the prediction of complex DDIs involving enzymes, transporters, and multiple interaction mechanisms Reki c et al, 2011;Varma et al, 2012Varma et al, , 2013Dhuria et al, 2013;Gertz et al, 2013Gertz et al, , 2014Guo et al, 2013;Kudo et al, 2013;Siccardi et al, 2013;Wang et al, 2013a;Sager et al, 2014;Chen et al, 2015;Shi et al, 2015). Furthermore, the mechanistic understanding of ADME changes that occur in different age groups or disease states has improved, and consequently PBPK modeling has been used to simulate drug disposition in special populations including hepatic (Johnson et al, 2014) and renal impairment populations (Li et al, 2012;Zhao et al, 2012a;Lu et al, 2014;Sayama et al, 2014), children (Leong et al, 2012), and pregnant women (Andrew et al, 2008;Gaohua et al, 2012;Horton et al, 2012;Ke et al, 2012Ke et al, , 2013Ke et al, , 2014Lu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to distinguish RI effects among drugs that undergo passive filtration, active reabsorption, and active tubular secretion. Although we did not examine this issue, Sayama et al 9. recently demonstrated that the changes in CL R were similar among these three types of renally eliminated drugs.…”
Section: Utilitymentioning
confidence: 88%
“…There are two major factors that might contribute to greater AUC increase for RI than for DDI with pharmacological inhibitors of renal transporters for drugs with f e ≥30%. The first factor to consider is that RI can affect not only active secretion, but also the glomerular filtration of drugs, as both processes appeared to be affected similarly in RI 9. The second factor is the lack of potent and specific inhibitors for renal transporters, and therefore the effect of complete transporter inhibition cannot be ascertained with pharmacologic inhibition studies.…”
Section: Utilitymentioning
confidence: 99%